A matched‐pair analysis of patients with medium‐sized prostates (50 cc) treated for male LUTS with HoLEP or TURP. Issue 2 (1st October 2019) - Magistro, Giuseppe; Westhofen, Thilo; Stief, Christian G.; Weinhold, Philipp
Abstract: Objectives: To evaluate perioperative parameters, early functional outcomes, and the safety profile in a matched‐pair analysis of lower urinary tract symptom (LUTS) patients treated with holmium laser enucleation of the prostate (HoLEP) or transurethral resection of the prostate (TURP). Methods: We conducted a retrospective, matched‐pair analysis of 2011 men treated for LUTS in our institution from 2013 to 2017. In the final analysis, 197 patients (HoLEP n = 97; TURP n = 98) were matched for prostate size (50 cc), age, and body mass index, and both cohorts were compared for demographic parameters, clinical outcomes, and adverse events according to the Clavien‐Dindo classification. Results: The perioperative assessment revealed a significantly higher tissue retrieval percentage of 75.4% (interquartile range [IQR] 64‐81.2) after HoLEP in comparison to 47.3% (IQR 40‐54.7) after TURP ( P <.001). A shorter surgery time was reported for TURP with a median time of 55.5 minutes (IQR 48‐70.5), whereas the median time for HoLEP was 62 minutes (IQR 51‐85) ( P =.006). The median improvements in International Prostate Symptom Score (IPSS) were 11 points (IQR 5.5‐17) and 7 points (IQR 3‐14) for HoLEP and TURP, respectively ( P =.007). Peak urinary flow rate (Qmax ) increased more after HoLEP (12.0 mL/s; IQR 7‐23) than after TURP (8.5 mL/s; IQR 5‐18.25) ( P =.028). With an overall incidence of adverse events of 6% (n = 6) compared to 16% (n = 16%), significantly fewer complications occurred after HoLEP than after treatment with TURP ( P <.05). Conclusions: HoLEP is not only an attractive alternative for the enucleation of larger prostates, but it must be considered a size‐independent technique with the potential to outdo the current reference method TURP.